Penerapan Otonomi Daerah Pada Sektor Pelayanan Dan Prinsip Good Governance (Studi Pada Pelayanan Terpadu Satu Pintu Di Kota Bekasi) - Hermansyah; Ismail; Lina, Ramlani (Acta Law Journal, 2022)
The Indonesian state is in the form of a unitary state, but in the regional government system it adheres to the principles of Federalism such as regional autonomy. Theoretically, regional autonomy is expected to encourage local democracy, bringing the state closer to the people. In addition, regional autonomy can create better public services. This study aims to find out how the implementation of regional autonomy arrangements in the one-stop integrated service sector in Bekasi City and knowing how public service efforts, especially licensing services in Bekasi City are related to the principles of good governance. The method used is a qualitative approach, which aims to describe situations, phenomena, or problems without having to change the meaning received in society or social groups receiving public services. The results of the study show that the application of regional autonomy regulations in the one-stop integrated service sector in Bekasi City, namely One-stop integrated services in the field of goods, services and administration run in accordance with the provisions in the Decree of the Mayor of Bekasi Number: 700/Kep.103-DPMPTSP/V/2017, concerning the Special Code of Ethics for Apparatus in the Investment Sector, and one-stop integrated services. Public service efforts, especially licensing services in Bekasi City, are related to the principles of Good Governance, namely Based on Government Regulation Number 5 of 2021 concerning Implementation of Risk-Based Business Licensing and Government Regulation Number 6 of 2021 concerning Implementation of Licensing.